Tantalisingly close : an archaeology of communication desires in discourses of mobile wireless media - De Vries, Imar O. (MediaMatters., 2012)
A number of recent studies of mobile wireless communication devices focus on use values, social implications, changing norms and ethics, conversation strategies and culture-dependent domestication. De Vries proposes to venture into a more historical and comparative direction to shed light on our preoccupation with them in the first place. He constructs an expanded archaeological view of the development, marketing, and reception of communication technologies over the past 200 years, providing a comprehensive account of how persistent paradoxical desires for sublime communication have come to gi.